Acquiring Hepatitis-C Viral Infection during Maintenance Hemodialysis Patients at DHQ Hospital Sheikhupura: : A Cross Sectional Study - Hussain, Yaris; Sabir, Anum; Naz, Saba; Munawar, Nazish; Anjum, Roshina (Pakistan Journal of Kidney Diseases, 2021)
Background: End stage kidney disease (ESKD) is one of the end results of chronic kidney disease. In center hemodialysis is the most common renal replacement therapy (RRT) for these patients used in Pakistan. It is associated with increased risk of health care-related infections. Hepatitis-C is the frequent blood born viral infection in hemodialysis center. Its frequency is very high in hemodialysis patients as compared to general and even to thalassemia population. Purpose of the study: To assess the gravity of Hepatitis-C viral infection in hemodialysis patients. Methods: A retrospective cross-sectional study done in dialysis center of DHQ hospital Sheikhupura, Punjab, Pakistan in January 2018. All the patients who had started hemodialysis with HCV negative status and had remained on hemodialysis for more than three months were included in the study. Patients with Hepatitis-C positive status, acute kidney disease and on dialysis less than three months were excluded. All patients were tested by enzymes linked immune-sorbent essay (ELISA) method for HCV status. Results: Out of 153 Hepatitis-C negative patients at the time of initiation of dialysis, 60 (39.21 %) converted positive while 93 (60.78 %) were still HCV negative by ELISA method at the time of study. Number of dialysis were having significant p value. Conclusion: Most of the patients had acquired Hepatitis-C infection during in-center hemodialysis. This emphasizes the importance of stringent infection prevention and control practices